The Global Burden of Maxillofacial Trauma in Critical Care: A Narrative Review of Epidemiology, Prevention, Economics, and Outcomes - Antonino Maniaci; Mario Lentini; Luigi Vaira; Salvatore Lavalle; Salvatore Ronsivalle; Francesca Maria Rubulotta; Lepanto Lentini; Daniele Salvatore Paternò; Cosimo Galletti; Massimiliano Sorbello; Jerome R Lechien; Luigi La Via (Medicina)
Background and Objectives: Maxillofacial trauma represents a significant global health challenge with substantial physical, psychological, and socioeconomic consequences. Materials and Methods: This narrative review analyzed 112 articles published between 2000 and 2024 examining epidemiology, prevention, economics, and outcomes of maxillofacial trauma in critical care settings. Results: Road traffic accidents remain the primary cause globally, followed by interpersonal violence and occupational injuries. Effective prevention strategies include seat belt laws, helmet legislation, and violence prevention programs. Economic burden encompasses direct healthcare costs (averaging USD 55,385 per hospitalization), productivity losses (11.8 workdays lost per incident), and rehabilitation expenses (USD 3800–18,000 per patient). Surgical management has evolved toward early intervention, minimally invasive approaches, and advanced techniques using computer-aided design and 3D printing. Complications affect 3–33% of patients, with significant functional disabilities and psychological sequelae (post-traumatic stress disorder in 27%, depression/anxiety in 20–40%). Conclusion: Maxillofacial trauma management requires multidisciplinary approaches addressing both immediate treatment and long-term rehabilitation. Despite technological advances, disparities in specialized care access persist globally. Future efforts should implement evidence-based prevention strategies, reduce care disparities, and develop comprehensive approaches addressing physical, psychological, and socioeconomic dimensions through collaboration among healthcare professionals, policymakers, and community stakeholders.